How does accreditation influence the dynamics of organizational identity for business schools? - Lejeune, Christophe; Schultz, Majken; Vas, Alain (Management international / International Management / Gestiòn Internacional, 2015)
Accreditation has become more prominent for business schools since two decades. In this paper, we explore how accreditation influences the internal and external processes of identity dynamics. First, we argue that Hatch & Schultz (2002) framework, social identity theory and the habitual routines approach offer a comprehensive theoretical framework. Second, we illustrate it with a European Management School’s accreditation failure and its management of change related to the accreditation goal. We elaborate and discuss a model titled “Identity Change through Accreditation” (ICA). Finally, we suggest some implications for managing change during accreditation as well as avenues for research.